Biobarriers for groundwater treatment a review. - Careghini, A.
Biobarriers (BBs) are a new type of in situ technology for the remediation of contaminated groundwater. In recent years, this remediation technique has been more and more used in place of traditional Pump & Treat systems or other in situ technologies both in the USA and Europe. This work reviews the main experiences of BBs. The literature contains reports about tests and application at different scales (laboratory, pilot and full scale), which have been analyzed according to the aim of the study, the operative conditions adopted, the filling material, the inoculation procedure, the electron acceptor and the nutrient delivery systems. Operative conditions were extremely varied. Lab scale experiments pointed out good results in terms of pollutant removal efficiency. Pilot scale tests and full-scale applications confirmed the results obtained at lab scale, but also pointed out the importance of design for a proficient remediation system. The experiences underlined some possible critical issues: (a) the filling material must ensure proper hydraulic properties, but it also must be capable of keeping biomass in the reactive zone; (b) inoculation is a critical step and measurements should be carried out to check the initial distribution of microorganisms and its evolution over time; (c) electron acceptor and nutrient supply is usually required, but oxygenation into anaerobic aquifers can be critical.
Keywords: Biobarrier; Groundwater; Remediation